Urban Agriculture Europe. - (:unkn) unknown (Jovis, 2016)
How can agriculture contribute to the sustainable development of European cities? How can agriculture and horticulture create vital urban spaces that have new social and ecological qualities and are also economically viable? "Urban Agriculture Europe" is the first comprehensive, transdisciplinary publication about urban agriculture in Europe. Apart from well-known examples of urban food gardens in Western European metropolises, this volume also studies innovative forms of agriculture on the urban periphery, bringing in experiences in Eastern and Southern Europe. The contributions approach urban agriculture from the point of view of social science, the economy, agricultural ecology, and spatial planning and address the role of citizens, involved parties, and politics, as well as operational models and planning tools. Case studies from Barcelona, Dublin, Geneva, Milan, Sofia, Warsaw, and the Ruhr Metropolis allow a comparative view of European practice. Statements from involved parties and guidance for cities and regions round off the publication.
Keywords: Stadtraum; Stadt; Landwirtschaft; Brachfläche; Landwirtschaftliche Nutzfläche; Agrarproduktion; Gartenbau; Privatwirtschaft; Fallstudie; Stadtgrün; Governance; Zivilgesellschaft; Urban agriculture; Klimaschutz